Gene Expression, Biochemical Characterization of a sn-1, 3 Extracellular Lipase From Aspergillus niger GZUF36 and Its Model-Structure Analysis - Xing, Shuqi; Zhu, Ruonan; Cheng, Kai; Cai, Yangyang; Hu, Yuedan; Li, Cuiqin; Zeng, Xuefeng; Zhu, Qiujin; He, Laping (Frontiers in Microbiology, 2021)
In this study, a sn-1, 3 extracellular lipases from Aspergillus niger GZUF36 (PEXANL1) was expressed in Pichia pastoris, characterized, and the predicted structural model was analyzed. The optimized culture conditions of Pichia pastoris showed that the highest lipase activity of 66.5±1.4 U/mL (P < 0.05) could be attained with 1% methanol and 96 hours induction time. The purified PEXANL1 exhibited the highest activity at pH 4.0 and 40 °C temperature, and its original activity remained unaltered in the majority of the organic solvents (20% v/v concentration). Triton X-100, Tween 20, Tween 80, and SDS at a concentration of 0.01% (w/v) enhanced, and all the metal ions tested inhibited activity of purified PEXANL. The results of ultrasound-assisted PEXANL1 catalyzed synthesis of 1,3-diaglycerides showed that the content of 1,3-diglycerides was rapidly increased to 36.90% with 25 min of ultrasound duration (P < 0.05) and later decreased to 19.93% with 35 min of ultrasound duration. The modeled structure of PEXANL1 by comparative modelling showed α/β hydrolase fold. Structural superposition and molecular docking results validated that Ser162, His274, and Asp217 residues of PEXANL1 were involved in the catalysis. Small-angle X-ray scattering analysis indicated the monomer properties of PEXANL1 in solution. The ab initio model of PEXANL1 overlapped with its modeling structure. This work presents a reliable structural model of Aspergillus niger lipase based on homology modeling and small-angle X-ray scattering. Besides, the data from this study will benefit the rational design of suitable crystalline lipase variants in the future.